In Search of Law in Women’s and Gender Studies: Toward Critical Womanist Legal Studies - Kessler, Mark (Atlantis, 2016)
In the context of recent critiques of Women’s and Gender Studies’ (WGS) institutionalization within the academy, this article foregrounds the role that a transdisciplinary and critical womanist legal studies may play in addressing some of the most significant concerns. It discusses the contours of a research approach, building on previous work in WGS as it intersects with critical legal scholarship from other locations in the academy with similar goals, purposes, and commitments to social justice. It also assesses the extent to which legal studies are evidenced in current published works in WGS journals and emphasizes how an increased emphasis on such scholarship permits researchers to usefully explore significant concerns in the field, including the operation of power and privilege, possible interventions in dominant cultural discourses, and legal constructions of intersecting roles of race, gender, class, and sexuality. Further, the article suggests that transdisciplinary critical womanist legal studies may help to address concerns that the successful institutionalization of WGS has narrowed the field’s focus, blunted its critical edge, and separated academic work from grassroots communities and political action.